Sweet or not: Using information and cognitive dissonance to nudge children toward healthier food choices - Nguyen, Trang; de Brauw, Alan; Berg, Marrit van den (Elsevier, 2022)
In the interest of public health, it is important to nudge children toward healthier food choices (e.g., beverages with less added sugar). We conducted a field experiment in a peri-urban region in Vietnam to evaluate the effects of information and cognitive dissonance on the food choices of children. Our sample consisted of more than 1200 primary school children, randomly assigned into three groups: control, health information, and health information plus hypocrisy inducement. The third group was intended to raise cognitive dissonance by illustrating the gap between what people know they should do (socially desired behaviors) and what they actually do (transgressions). The results indicate that health information increased the likelihood of selecting milk with less sugar by around 30 %, as compared to the control group. Hypocrisy inducement did not make any additional contribution to healthier food choices. The treatment effects declined when there was a delay between the treatment and the behavioral choice. We discuss the practical implications of our findings for short-term intervention field studies.